Gaya Hidup, Persepsi, dan Pengaruhnya Terhadap Keputusan Penggunaan E-Wallet (Studi Pada Mahasiswa Prodi Ekonomi Syariah IAIN Kediri Angkatan 2019-2022) - Marbiyanti, Reni; Munif, Achmad; Fadilah, Adin; Utama, Yopi Yudha (Al-Muraqabah: Journal of Management and Sharia Business, 2024)
This study evaluates the influence of lifestyle and perception on the decision to use the electronic wallet ShopeePay among students of Islamic Business 2019-2022 IAIN Kediri. Quantitative methods are used with a population of 642 students. In this study, 215 respondents were selected through purposive sampling. The analysis conducted includes descriptive statistical tests, instrument tests, classical acceptance tests, multiple linear regression analysis and hypothesis tests. The results show that lifestyle has a positive influence of 0.320 on the decision to use the ShopeePay e-wallet. Perceptions also have a positive influence on the decision to use the ShopeePay e-wallet (0.838). The T-test shows that lifestyle has a significant influence on the decision to use the ShopeePay e-wallet, with a t-value of 3.311, which is greater than the t-table of 1.971. In addition, the Pearson correlation value between lifestyle and the decision to use the ShopeePay e-wallet is 0.607. The effect of lifestyle on the use of ShopeePay wallets shows a strong correlation (r = 0.723, t = 9.098> t-table = 1.971). The effect of perception on the decision to use ShopeePay e-wallet is significant (p <0.05) among 2019-2022 Islamic economics students. Based on the determination analysis, lifestyle and perception have a significant influence on the decision to use the ShopeePay e-wallet at 54.6%. The remaining 45.4% is influenced by other variables not investigated in this study.